PENILAIAN DAUR HIDUP BOTOL PET (POLYETHYLENA TEREPHTALATE) PADA PRODUK MINUMAN LIFE CYCLE ASSESSMENT (LCA) OF PET (POLYETHYLENA TEREPHTALATE) BOTTLES FOR DRINKING PRODUCT - Mohamad Yani (Bumi Lestari Journal of Environment, 2013)
AbstractThe use of PET packaging in drinking products has increased and shifted glass packaging,so it is necessary to study the life-cycle of PET packaging. This research aims to evaluate lifecycle of PET bottles on tea beverage products. This life-cycle assessment includes productionprocess, inventory, environmental impact, and cost analysis. The life cycle of PET bottle inIndonesia is not complete. The relationship between PET bottle manufacturers, drinkingmanufacturers, and recycling waste, are unidirectional. The recycled waste-PET used forother products. Based on the analysis of inventory, PET bottles 600ml is nedeed 28g resin/bottles and energy. The PET packaging production still produced a high defective product.Environmental impact assessment of PET bottle production indicates that the ambient airquality, noise and waste water are still good. The impact of PET bottle plant produce aglobal warming potential, reduce ozone layer and acid rain. The cost analysis describethat selling price of PET bottles is half the price of a glass bottle, while the price of waste-PET flake is three times higher than cullet. Although PET packaging is considered morepractical, cheap and saving, but the recycling of PET packaging has not been widelyutilized.